The role of cardiac transcription factor NKX2-5 in regulating the human cardiac miRNAome - Arasaratnam, Deevina (Sci Rep, 2019)
MicroRNAs (miRNAs) are translational regulatory molecules with recognised roles in heart development and disease. Therefore, it is important to define the human miRNA expression profile in cardiac progenitors and early-differentiated cardiomyocytes and to determine whether critical cardiac transcription factors such as NKX2-5 regulate miRNA expression. We used an NKX2-5(eGFP/w) reporter line to isolate both cardiac committed mesoderm and cardiomyocytes. We identified 11 miRNAs that were differentially expressed in NKX2-5 -expressing cardiac mesoderm compared to non-cardiac mesoderm. Subsequent profiling revealed that the canonical myogenic miRNAs including MIR1-1, MIR133A1 and MIR208A were enriched in cardiomyocytes. Strikingly, deletion of NKX2-5 did not result in gross changes in the cardiac miRNA profile, either at committed mesoderm or cardiomyocyte stages. Thus, in early human cardiomyocyte commitment and differentiation, the cardiac myogenic miRNA program is predominantly regulated independently of the highly conserved NKX2-5 -dependant gene regulatory network.